Rules and Victims - Hoskins, Geoffrey (Cambridge The Belknap Press of Harvard University Press, 2006)
With particular attention to non-Russian regions and ethnic groups and to Russia`s relations with neighbouring polities, Geoffrey Hosking lays out the links between political, economic, social, and cultural phenomena that have made Russia what it is a world at once familiar and mysterious to Western observers.
Keywords: History